The heart of George MacDonald a one-volume collection of his most important fiction, essays, sermons, drama, poetry and letters - MacDonald, George 1824-1905; Hein, Rolland (Wheaton, IL Harold Shaw, 1994)
Includes bibliographical references.
Keywords: MacDonald, George, -- 1824-1905; Christian fiction